Advances in the mechanisms of action of cancer-targeting oncolytic viruses - Lin, Cun-Zhi (Oncol Lett, 2018)
Cancer virotherapy mediated by oncolytic viruses (OV), has emerged as a novel and effective strategy in cancer therapeutics. Preclinical models have demonstrated anticancer activity against numerous types of cancer. Currently, a number of recombinant viruses are in late phase clinical trials, many of which have demonstrated promising results regarding the safety and reliability of the treatments, particularly when combined with standard antineoplastic therapies. In addition to molecular-targeted therapeutics, genetic engineering of the viruses allows functional complementation to chemotherapy or radiotherapy agents. Co-administration of chemotherapy or radiotherapy is imperative for an effective treatment regime. Additionally, these approaches may be used in combination with current treatments to assist in cancer management. The near future may reveal whether this renewed interest in oncological virotherapy will result in meaningful therapeutic effects in patients. The aim of the present review was to highlight how the knowledge of oncolytic viral specificity and cytotoxicity has advanced in recent years, with a view to discuss OV in clinical application and the future directions of this field.